Psychometric properties of the Chinese Version of the Readiness for Hospital Discharge Scale for people living with HIV - Chen Chen; Xiaoxia Zhang; Chulei Tang; Xueling Xiao; Zirong Tao; Honghong Wang (Elsevier, 2020)
Objective: The study was conducted to validate the reliability and factor structure of the Chinese version of the Readiness for Hospital Discharge Scale (RHDS-CH) for people living with HIV (PLWH). Methods: From May 2017 to November 2017, a cross-sectional survey was performed in two AIDS inpatient departments located in two cities in Hunan, China. Reliability was evaluated by examining the internal consistency and split-half reliability of the items. A confirmatory factor analysis was performed to assess the factor structure of the RHDS-CH, and the model was revised according to the modification index. Results: Cronbach's α for the RHDS-CH was 0.912, and the split-half reliability of the total scale was 0.831. Initially, the results of the confirmatory factor analysis indicated that the sample did not fit this four-factor model and its 23 items well (χ2/df = 3, GFI =0.772, TLI = 0.823, CFI = 0.844, RMSEA = 0.100). To improve the model fit indices, we performed model modification with the guidance of modification indices. Finally, the model fit indices showed an acceptable fit to the data (χ2/df = 2.141, GFI = 0.844, TLI = 0.899, CFI = 0.915, RMSEA = 0.075). Coefficients of corrected item-total correlation of the RHDS-CH ranged from 0.435 to 0.726. Conclusion: This study is the first to examine the psychometric properties of the RHDS-CH for PLWH. Our findings showed good reliability and confirmed the four-factor structure model for PLWH.